2010
DOI: 10.1007/s00436-010-2043-3
|View full text |Cite
|
Sign up to set email alerts
|

Repellent and acaricidal effects of botanical extracts on Varroa destructor

Abstract: Extracts of indigenous plants from South America have shown a broad spectrum of bioactivities. No-contaminant and natural substances have recently resurged as control treatment options for varroosis in honey bee colonies from Argentina. The aim of this work was to evaluate the biological activity of botanical extracts from Baccharis flabellata and Minthostachys verticillata on Varroa destructor and Apis mellifera. The acaricidal and insecticidal activities were assessed by the spraying application method. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Bee researchers and beekeepers have developed and tested numerous biological or biotechnical methods to control this mite, including drone brood removal (Wantuch and Tarpy 2009), which is labor intensive, screens on bottom boards (Harbo and Harris 2004;Delaplane et al 2005), and dusting with a powder such as flour or powdered sugar (Fakhimzadeh 2001), methods which have not always been found effective (Ellis et al 2009;Rosenkranz et al 2010). The most common approach (and until recently the most effective) has been chemical control, which includes synthetic miticides and organic acids as well as plant essential oils (e.g., Ruffinengo et al 2002;Eguaras et al 2005;Damiani et al 2010). Given the damage that V. destructor can do to individual bees and entire colonies, beekeepers seek a control strategy that does not require either intensive hive manipulation or multiple applications of chemicals to beehives, which has inherent risks of honey and wax contamination, bee toxicity, and pest resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Bee researchers and beekeepers have developed and tested numerous biological or biotechnical methods to control this mite, including drone brood removal (Wantuch and Tarpy 2009), which is labor intensive, screens on bottom boards (Harbo and Harris 2004;Delaplane et al 2005), and dusting with a powder such as flour or powdered sugar (Fakhimzadeh 2001), methods which have not always been found effective (Ellis et al 2009;Rosenkranz et al 2010). The most common approach (and until recently the most effective) has been chemical control, which includes synthetic miticides and organic acids as well as plant essential oils (e.g., Ruffinengo et al 2002;Eguaras et al 2005;Damiani et al 2010). Given the damage that V. destructor can do to individual bees and entire colonies, beekeepers seek a control strategy that does not require either intensive hive manipulation or multiple applications of chemicals to beehives, which has inherent risks of honey and wax contamination, bee toxicity, and pest resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanolic extracts of Baccharis flabellate Hook & Arn (baccharises) and Minthostachys verticillata (Griseb.) Epling (peperina) have been shown to be highly effective against mites, and their applications did not have a negative effect on bees (Damiani et al, 2011). As essential oils positively affect the caring behaviour of honey bee colonies against varroa (Abd El Wahab, Ebadah, & Zidan, 2012), it has been reported that the concentration of 21.1% of neem seed oil (Azadirachta indica) led to 100% mortality percentage of Varroa mites after 72 hours (González-Gómez, Otero-Colina, Villanueva-Jiménez, Peña-Valdivia, & Santizo-Rincón, 2012).…”
Section: Studies On Bee Health Of Medicinal Aromatic Plants and Oilsmentioning
confidence: 99%
“…To lower the hazardous effects caused by V. destructor , several plant extracts have been found to be extremely effective. These are Groundsel bush ( Baccharis flabellate ), Peperina (Minthostachys verticillata) (Damiani et al, 2011), Pepperwort (Lepidium latifolium) (Razavi et al, 2015), Thymol (Thymus kotschyanus) (Ghasemi et al, 2011), Laurel (Laurus nobilis), thyme (Damiani et al, 2009), savory, spearmint (Ariana et al, 2002).…”
Section: A Novel Application Of Plant Extracts Against Honey Bee Pathmentioning
confidence: 99%